PROPOFOL VERSUS PLACEBO FOR PREVENTION OF EMESIS DURING SPINAL ANAESTHESIA - Boujan, Amir M. Khudadad (European Scientific Journal, ESJ, 2015)
Background: Spinal anesthesia has been shown to be an easy, rapid and safe technique, nevertheless, it has some minor side effects, including intraoperative nausea and vomiting. Nausea, retching, and vomiting during regional anesthesia are common occurrences. The abrupt diaphragmatic contractions, present in emesis, are uncomfortable to the patient and may cause protrusion of the abdominal viscera, rendering surgery more difficult and increasing the risk of visceral injuries. Objectives: evaluation the effectiveness of low dose propofol for control of nausea and vomiting during spinal anesthesia. Patients and Method: After taking written informed consent, 83 Patients (79 males and 4 females) of ASA physical status I or II, aged 23-80 years, scheduled for elective urosurgery in the Sulaimani teaching hospital were enrolled in a single blind prospective study. Patients were divided into two groups to receive either propofol (1 mg/kg/hr) or Intralipid (Placebo). Operations were performed under spinal anaesthesia. Patients were followed up for 24 hours for post operative nausea and vomiting. Results: Patients who received Propofol had statistically significant less nausea and vomiting than those who received Placebo (Intralipid). Conclusion: Propofol at a subhypnotic dose is effective in the prevention of nausea and vomiting.